2016
DOI: 10.1093/gastro/gow005
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening in African Americans: practice patterns in the United States. Are we doing enough?

Abstract: Background: Colorectal cancer (CRC) is a common form of malignancy and a leading cause of death in the United States. Screening decreases CRC incidence and mortality. African Americans are at an increased risk of developing CRC, and recommendations are to initiate screening at the age of 45. This study aims to assess the rate of screening for colorectal cancer in African Americans between the ages of 45–49.Methods: African Americans between the ages of 45–49 were identified in the Explorys national database. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…These features may enable colonoscopy to be a reliable tool for the early detection of CRC and also allow prevention of the progression of other lesions to CRC. Many Western countries include colonoscopy in their CRC screening programs [ 13 , 14 ]. Although the program was widely advertised before the start of screening, our reported colonoscopy compliance rate was unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…These features may enable colonoscopy to be a reliable tool for the early detection of CRC and also allow prevention of the progression of other lesions to CRC. Many Western countries include colonoscopy in their CRC screening programs [ 13 , 14 ]. Although the program was widely advertised before the start of screening, our reported colonoscopy compliance rate was unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a myriad of research pointing to sub-optimal cancer screening and cancer-related mortality rates in Latinas and Black/African American women [7, 14, 18], there is very little qualitative data available on what could be done to improve cancer screening uptake and perhaps ultimately improve mortality rates in these populations. The voices heard from these focus groups do not generate easy answers for the amelioration of these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…And yet, a number of barriers to cancer screening have been identified, including cost, fear, trust, time and lack of knowledge [1013]. These barriers have been highlighted as a major contributor to the lower cancer screening rates for Latinas and Black/African American women [1416], and higher mortality rates for certain cancers, including breast and colon, among Black/African American women [17] and cervical among Latinas [18]. …”
Section: Introductionmentioning
confidence: 99%
“…12 A study using claims data on more than 180,000 blacks showed only 17.4% in those ages 45À49 years had been screened. 13 In a South Carolina Federally Qualified Health Center (FQHC) CRC screening program, in which 71% of 665 participants were black, and 29% were male, the adenoma detection rate among those aged 45À49 years was 26%. 14 However, the diagnostic and therapeutic yield of CRC screening in this age group is understudied.…”
Section: Research On Colorectal Cancer Screening Among Blacks With Amentioning
confidence: 99%